Nurses’ knowledge and attitude towards children pain management: a multi-site survey study - Fenta, Efrem; Kibret, Simegnew; Hunie, Metages; Tamire, Tadese; Eshetie, Denberu; Seid, Shimelis; Fentie, Yewlsew; Amaha, Eleni; Desse, Tiruwork; Dejen, Bantayehu; Essa, Keder; Teshome, Diriba (Frontiers in Pediatrics, 2023)
Background: Adequate children's pain management is universally considered an ethical obligation. In evaluating and treating children's pain, nurses invest more time and take a leading role. This study aims to assess nurses’ knowledge and attitudes towards children’s pain management. Materials and Methods: A convenience sample of 292 nurses working at four South Gondar Zone hospitals of Ethiopia was surveyed. The Pediatric Nurses Knowledge and Attitudes Survey regarding pain was used to collect data from study participants. Data were descriptively (frequency, percentage, mean, and standard deviation) and inferentially (Pearson correlation, one-way between-groups analysis of variance, and independent-samples t-test) analyzed. Results: The majority of the nurses (74.7%) had insufficient knowledge and attitude (PNKAS score <50%) regarding pediatric pain management. The mean ± SD correct answer score of 43.1% ± 8.6% was achieved by nurses. An increase in pediatric nursing experience was significantly correlated with nurses’ PNKAS score (p <0.001). There was a statistically significant difference in the mean PNKAS scores of nurses who had official pain management training as compared to its counterparts (p 0.001). Conclusion: Nurses who are working South Gondar Zone of Ethiopia have insufficient knowledge and attitudes regarding pediatric pain management. Therefore, there is an urgent need for in-service training in pediatric pain management.